Fa’āliyah Istikhdām al-Kharītah al-Żihniyyah fī Ta’līm Qawā’id al-Lugah al-‘Arabiyyah li Țullāb al-Madrasah al-Śānawiyyah - Ramadhani, Rifky Kamila; Salma, Kunti Nadiyah; Ana, Sri (Study Program of Arabic Language Teaching, 2025)
This research examines the application of mind mapping in Arabic grammar learning and its effectiveness in improving students' understanding. The hypotheses in this study are H₀, namely that the use of mind mapping has no significant effect on students' understanding of Arabic grammar learning, and Hₐ (alternative hypothesis), namely that the use of mind mapping significantly affects students' understanding of Arabic grammar learning. This research uses a quantitative approach with a one-group pretest-posttest design. The population in this study consists of all 9th-grade students at MTs YPI Manbaul Ulum Semanding Jenangan Ponorogo in the 2023/2024 academic year, totaling 20 students, and the entire population was used as the sample through a saturated sampling technique. The data sources consist of primary data, 9th-grade students, and secondary data from textbooks, teacher notes, and curriculum references. Data collection techniques include observation, interviews, tests, and documentation. Data analysis techniques involve the normality test (Shapiro-Wilk), homogeneity test, and paired sample t-test using SPSS 16 to measure the effectiveness of the mind mapping strategy. The results of the study indicate that the use of mind mapping in learning Arabic grammar is effective. This is evidenced by the significance value (Sig. 2-tailed) in the paired sample t-test of 0.00 < 0.05, which means H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that the application of mind mapping in Arabic grammar learning significantly improves students' understanding.